Influence of pharmaceutical marketing mix strategies on physicians' prescribing behaviors in public and private hospitals, Dessie, Ethiopia: a mixed study design - Abel Demerew Hailu; Birhanu Demeke Workneh; Mesfin Haile Kahissay (BMC, 2021)
Abstract Background Prescription drugs constitute the primary source of revenue for the pharmaceutical industry. Most pharmaceutical companies commit a great deal of time and money to market in hopes of convincing physicians about their products. The objective of this study is to assess perceived influence of pharmaceutical marketing mix strategies on physicians' prescribing behaviors in hospitals, Dessie, Ethiopia. Methods Mixed methods sequential explanatory design was employed in two public and three private hospitals. A cross-sectional study design was employed by including (136) physicians working in public and private hospitals. Percentage, mean, standard deviation, and multiple linear regressions were computed using Statistical Package for Social Science. In the second phase, the phenomenological design was employed to fully explore in-depth information. Purposive sampling was used to select key informants and 14 in-depth interviews were conducted by the principal investigator. Content analysis was performed using Nvivo 11 plus and interpretation by narrative strategies. Results The overall perceived influence of pharmaceutical marketing mix strategies in physicians' prescribing behavior was 55.9%. The influence of promotion, product, place and price strategy perceived by physicians in their prescribing behavior was 83 (61%), 71(52.2%), 71 (52.2%), 80 (58.8%) respectively. There was a statistically significant difference among marketing mix strategies (β = 0.08, p = < 0.001). Determinants on the influence of physicians' prescribing behavior were specialty (p = 0.01) and working areas (p = 0.04). The qualitative design also generates additional insights into the influence of pharmaceutical marketing mix strategies on physician prescribing behavior. Conclusions More than half of physicians perceived that pharmaceutical marketing mix strategies influence their prescribing behavior. The qualitative design also revealed that pharmaceutical marketing mix strategies influenced physicians prescribing behavior. Strengthening the regulation and maintaining ethical practice would help to rationalize the physicians' prescribing practice.